PHOTOTHERAPY AND PHOTODYNAMIC THERAPY IN THE TREATMENT OF EXTRAGENITAL LICHEN SCLEROSUS - O. O. Katz; F. A. Trifonov; V. V. Kuznetsov (Исследования и практика в медицине, 2015)
Abstract:Lichen sclerosus is a chronic inflammatory disease of the skin and mucous membranes coated with squamous nonkeratinizing epithelium. The etiology of this disease is not completely clear. The exact prevalence of the disease is quite difficult to establish due to a lack of awareness of medical staff about the disease and relatively few patients visit medical specialists. Many researchers lean towards autoimmune theory of the origin of the disease. This is the basis for the most common methods of treatment. We have the information that lichen sclerosus may be caused by trauma, hormonal disorders and infectious lesions. In some cases genetic predisposition is observed. Standard treatment for lichen sclerosus is the topical application of glucocorticosteroids. If this treatment is ineffective topical calcineurin inhibitors are used. However, in many cases both treatments of lichen sclerosus are ineffective. In response to the problem alternative therapies can be used. Efficiency of phototherapy and photodynamic therapy for some cutaneous diseases is well known, in this regard it is important to examine in depth possibilities of these methods for treatment of lichen sclerosus.